Eco-Balanced Scorecard as a Supporting Tool in EMAS System - Szyszka , Beata; Matuszak-Flejszman, Alina (Studia Oeconomica Posnaniensia, 2016)
Nowadays, one of a company's priorities is to build its image as responsible and environmental-friendly. Environmental management systems such ISO 14001 or EMAS (Eco-management and Audit Scheme) are tools that help organizations in creating such a picture. Implementing abovementioned systems enjoys popularity since the mid-90s. However, in some organizations, implemented systems suffer problems, and consequently, they are not as effective as expected. In many cases, systems are run at the operating level and often are not sufficiently linked with strategic management and planning. Integration of environmental objectives into the organization's strategy plays a significant role and may be provided by using the widely-known tool BSC (Balanced Scorecard), modified for environmental use. The aim of this article is to present examples of the integration of organizations' environmental objectives with four BSC perspectives. Researches are based on case study analysis obtained from secondary data sources (organizations' environmental statements). Results indicate that the most environmental objectives are posed in the area of internal processes, and the least in the area of finance. Additionally, it has been noted that there is a disproportion between the number of operational objectives and management objectives, which confirms that many environmental management systems are run at the operating level.